The face of crime: Apparent happiness differentiates criminal and non-criminal photos. Issue 4 (4th July 2021) - Sheldon, Kennon M.; Corcoran, Mike; Trent, Jason
ABSTRACT: In two studies we tested the hypothesis that observers can accurately distinguish between convicted criminals and matched controls, merely by scrutinizing facial photographs. Based on the Eudaimonic Activity Model, we further hypothesized that criminals and non-criminals differ in their apparent emotional positivity. Finally, based on honest signaling theory, we hypothesized that such emotionality differences can explain observers' ability to distinguish criminals and non-criminals. In Study 1 participants evaluated photos of people later convicted of crimes, and photos of matched controls. In Study 2 participants evaluated photos of Catholic priests later convicted of sexual offenses, and photos of the priests who replaced them at their parishes. All three hypotheses were supported. Furthermore, in Study 2, participants' own facial photos were rated by assistants. Consistent with honest signal theories, observer's facial positivity, as well as their self-rated positive affect, predicted their ability to perceive positive emotions in non-criminal faces.